PENGARUH LABA BERSIH, LAPORAN ARUS KAS OPERASI, DAN UKURAN PERUSAHAAN TERHADAP TINGKAT PENGEMBALIAN SAHAM - Rosadi Ahmadi; Darlis Edfan; Hariadi Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to determine the effect of net income, operating cashflow, and firm size on the stock return of the mining sector on the Indonesia StockExchange (IDX) for the period 2013-2016. Data derived from the annual financialreports of 30 mining sector companies. Data analysis used multiple linearregression analysis which was processed using SPSS version 16 software. Theresults of the research showed that net income and operating cash flow have asignificant effect on the rate of return. This indicates that investors considerinformation on net income and operating cash flow statements disclosed in theirannual reports to make investment decisions. While company size does not have asignificant effect on stock returns. The results of the calculation of the coefficientof determination (R2) that the percentage of the effect of net income, operatingcash flow, and the size of the company on the stock returns is 18.5%. While theremaining 81.5% is influenced by other variables not included in this regressionmodel.Keywords : Net Profit, Operating Cash Flow, Company Size, and Stock ReturnRate.